The Matrix Metalloproteases and Endothelin-1 in Infection-Associated Preterm Birth - Nicole S. Olgun; Sandra E. Reznik (Obstetrics and Gynecology International)
Preterm birth (PTB) is clinically defined as any delivery which occurs before the completion of 37 weeks of gestation, and is currently the most important problem in obstetrics. In the United States, PTB accounts for 12-13% of all live births, and, with the exception of fetuses suffering from anomalies, is the primary cause of perinatal mortality. While the risk factors for PTB are numerous, the single most common cause is intrauterine infection. As there is currently no FDA-approved therapy for infection-associated PTB, understanding the pathogenesis of preterm labor (PTL) and delivery should be given high priority. The matrix metalloproteinases (MMPs) are a family of enzymes that have been implicated in normal parturition as well as infection-triggered rupture of membranes and preterm birth. Several lines of evidence also suggest a role for endothelin-1 (ET-1) in infection-associated preterm delivery. This paper focuses on the evidence that the MMPs and ET-1 act in the same molecular pathway in preterm birth.